Laboratory Works with Digital Resources… – Motivative Means of Research for High Schools Pupils in Biology - Placinta, Daniela; Coropceanu, Eduard (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The teacher’s competence to select the most efficient methods, necessary for research using digital tools, is an imperative of modern didactics. The combination of digital skills and research methods helps pupils get involved in investigating the living world. Digital sensors enhance the applicative and interdisciplinary nature of laboratory work in Biology. The recorded results help young researchers discover scientific truths of processes and phenomena in nature. The conclusions formulated generate existing reflections on the processes and phenomena in the surrounding reality. Thus, we can mention that the digital Biology laboratory improves the quality of the instructive-educational process of the Biology discipline.